Klímaváltozás - aridifikáció - változó tájak = Climate change - aridification - changing landscape - Rakonczai János (2006)
The effects of globalisation are becoming more and more obvious not only in the world economy but also in the natural processes. In the international scientific world the effects of global warming can be observed the most in aridification process but many scientists presume connection with the increasingly unpredictable flood events, too. Few think, however, that the changed climate of the several decades – through the change of water cycle – can be resulted in the transformation of the natural landscape. The most important long term effect is the decrease of ground water. The decrease of ground water, however, influences processes through many interactions. On the one hand deeper ground water level causes that vegetation can hardly reach and utilise it which results in a decrease in biomass and in case of more significant transformation vegetation change can occur. On the other hand the change of ground water modifies the vertical movement of water and salt in soils, which results in the genetic transformation of soils. In the consequences of aridification processes may start or in case of arid soils they may generate a process that decreases salt. In both cases the change in the quality of the soil accompanies with the transformation of the natural vegetation.